Effects of pressure work on natural convection flow around a sphere with radiation heat loss - Akhter, T.; Alim, M. A. A. (Nonlinear Analysis: Modelling and Control, 2010)
The effects of pressure work with radiation heat loss on natural convection flow on a sphere have been investigated in this paper. The governing boundary layer equations are first transformed into a non-dimensional form and the resulting nonlinear partial differential equations are then solved numerically using finite-difference method with Keller-box scheme. We have focused our attention on the evaluation of shear stress in terms of local skin friction and rate of heat transfer in terms of local Nusselt number, velocity as well as temperature profiles. Numerical results have been shown graphically and tabular form for some selected values of parameters set consisting of radiation parameter Rd, pressure work parameter Ge, surface temperature parameter θw and the Prandtl number Pr.
Keywords: thermal radiation; Prandtl number; natural convection; pressure work